Zgodovina imenoslovja v Sloveniji - Šivic-Dular, Alenka (Jezikoslovni zapiski, 2002)
The article is a systematic and exhaustive discussion on the history of onomastics in Slovenia, which is presented in the following chapters: Onomastic corpora, Linguistic treatment of proper names, The institutional status of onomastics, The status of onomastics in relation to other linguistic branches, The most important achievements in Slovenia, The biographies of the most prominent scientists (Franc Miklošič, Luka Pintar, Fran Ramovš, France Bezlaj), The most frequently applied onomastic theories in Slovenia, The typologies of proper names used, The research methods employed, and their evolution, The relation between the methods used in Slovenia and theoretical achievements of onomastics as a global space, The unity of onomastic terminology, The relation to international terminology from 1983, The status of research - a general overview, The status of the research basis, Dictionaries and monographs.
Keywords: Slovene; slovenščina; onomastics; onomastika; Slovenia; Slovenija; zgodovinski prikazi